OBT analysis method using polyethylene beads for limited quantities of animal tissue. (August 2015) - Kim, S.B.; Stuart, M.
Abstract: This study presents a polyethylene beads method for OBT determination in animal tissues and animal products for cases where the amount of water recovered by combustion is limited by sample size or quantity. In the method, the amount of water recovered after combustion is enhanced by adding tritium-free polyethylene beads to the sample prior to combustion in an oxygen bomb. The method reduces process time by allowing the combustion water to be easily collected with a pipette. Sufficient water recovery was achieved using the polyethylene beads method when 2 g of dry animal tissue or animal product were combusted with 2 g of polyethylene beads. Correction factors, which account for the dilution due to the combustion water of the beads, are provided for beef, chicken, pork, fish and clams, as well as egg, milk and cheese. The method was tested by comparing its OBT results with those of the conventional method using animal samples collected on the Chalk River Laboratories (CRL) site. The results determined that the polyethylene beads method added no more than 25% uncertainty when appropriate correction factors are used. Highlights: Polyethylene beads method for OBT determination in animal tissues and animal products were determined. The method reduces process time. The polyethylene beads method added no more than 25% uncertainty when appropriate correction factors are used.